INFORMS general meeting 2024: digital sphere unity / Muhammad Amierul Haqeem Mohd Faizan and Nur Filzatul Najwa Yahya - Mohd Faizan, Muhammad Amierul Haqeem; Yahya, Nur Filzatul Najwa (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
On March 22, 2024, the INFORMS Society held its Annual General Meeting via Webex, from 2:15 PM to 4:05 PM. This virtual format, necessitated by three weeks of online classes for Ramadan and Eid, replaced the usual in-person gathering. Attendance was mandatory for first-semester students and strongly encouraged for others. The program began with the arrival of lecturers and students. The attendees, filled with patriotic fervor, joined together in singing the national anthem, Negaraku, and UiTM Di Hatiku. This was followed by a prayer led by Muhammad Zulfadhli bin Abdul Razak, seeking blessings and success for the duration of the program. INFORMS President Muhammad Amierul Haqeem bin Mohd Faizan gave a compelling speech, saying, "I take the issues that have arisen outside our School seriously, particularly regarding the respect and courtesy we must show towards our lecturers." He emphasized the importance of respect and ethics in academia for both academic and nonacademic staff.